Beyond deficit assessment in bilingual primary schools. Issue 3 (16th March 2022) - Knoester, Matthew; Meshulam, Assaf
ABSTRACT: In this paper, we analyze the harm that high-stakes standardized tests in the U.S. render to maintenance-oriented dual-language bilingual primary schools and, in particular, to minoritized bilingual learners. We argue that these schools must resist the negative incentives and prevailing logic that passing standardized tests is crucial for students' future success and act to mitigate the potential harm to their school missions and pedagogy that this form of assessment presents. The alternative anti-deficit qualitative approaches to assessment we describe here rely on assessments of student learning and knowledge that are strengths-based, culturally aware and mindful, and seek to motivate students to accomplish ambitious, albeit differentiated, goals. These assessments carry a tone of empowerment and cultural affirmation and foster positive academic identity development of emergent bilingual children. We hope here to persuade that these assessments will assist dual-language bilingual primary schools to resist the neoliberal pressure to tie high-stakes decisions to standardized testing, which impair the cultural, educational, and personal development of their most vulnerable students.